Weak versus strong dominance of shrinkage estimators - Giuseppe De Luca; Jan R. Magnus (Tinbergen Institute, 2021)
We consider the estimation of the mean of a multivariate normal distribution with known variance. Most studies consider the risk of competing estimators, that is the trace of the mean squared error matrix. In contrast we consider the whole mean squared error matrix, in particular its eigenvalues. We prove that there are only two distinct eigenvalues and apply our findings to the James–Stein and the Thompson class of estimators. It turns out that the famous Stein paradox is no longer a paradox when we consider the whole mean squared error matrix rather than only its trace.
Keywords: C13; C51; 330; Shrinkage; Dominance; James-Stein